Synthesis and Photoluminescence Properties of Ca5(PO4)3F: Ln (Ln: Dy3+, Eu3+ and Sm3+) Phosphors for near UV-based solid state lighting - Nandanwar, C.M.; Kokode, N.S. (Physics and Chemistry of Solid State, 2022)
The wet chemical synthesis of Ca5(PO4)2F host with lanthanide doped Dy3+, Eu3+ and Sm3+ was reported. The X-ray diffraction (XRD), structural and photoluminescence characteristics of phosphors were thoroughly investigated. The hexagonal system with the space group P 63/m (176) was verified by X-ray powder diffraction. Under UV excitation (352 nm), Ca5(PO4)2F:Dy3+ emits 481 nm (blue) and 575 nm (yellow), corresponding to 4F9/2→6H15/2 (magnetic dipole) and 4F9/2→6H13/2 (electric dipole) transitions, respectively. When Ca5(PO4)2F:Eu3+ phosphor was excited at 394 nm, the emission spectra showed strong bands at 591 nm (orange) and 614 nm (red). When excited at 403 nm, the emission spectra of Sm3+ activated Ca5(PO4)2F phosphor displayed emission peaks at 565 nm (yellow) and 599 nm (orange), respectively. The research analyses the photoluminescence characteristics of Ca5(PO4)3F: Ln (Ln: Dy3+, Eu3+ and Sm3+) as a possible material for near UV-based solid-state lighting.